A “novel” association to treat pain: tramadol/dexketoprofen. The first drug of a “new pharmacological class” - Fornasari, D.; Allegri, M.; Gerboni, S.; Fanelli, Guido (Acta Biomedica Atenei Parmensis, 2017)
Acute and chronic pain have an important socio-economical impact. In order to help physicians to choose the appropriate drug, especially for cancer pain, in 1986 WHO has developed a three-step analgesic “ladder” for cancer pain relief in adults. Later it has also been used for acute pain and chronic non-cancer pain. In step I nonsteroidal anti-inflammatory drugs (NSAIDs) are considered with or without adjuvants, in step II the use of weak opioids for mild-moderate pain, with or without NSAIDs and adjuvant, is suggested, while the step III is reserved to strong opioids for moderate-severe pain with or without non-opioids or adjuvants. In the last two decades, a better pathophysiology knowledge has improved pain management shifting our view from the pain ladder to a modern pain pyramid, in which drugs are selected not only on the basis of pain intensity, but mainly according to mechanisms underlying pain, including peripheral and spinal sensitization which is the main trigger of chronic pain. The best pharmacological approach has become multimodal, in which drugs belonging to different steps should be combined, matching the mechanisms of action with the type of pain. An important corollary of combining analgesic drugs with different mechanism of action is that proper matching achieves the same effect with lower doses, better outcome and fewer adverse effects. In this new perspective, fixed-dose pharmaceutical combinations of different drugs are very useful to fulfil pharmacodynamics, pharmacokinetics and adherence criteria, enriching the pain pyramid of half-steps between the first and second step and between the second and third step. Hence, a new fixed combination of a NSAID with peripheral and central anti-infilammatory activities, such as dexketoprofen, and a weak opioid, such as tramadol, with double analgesic activity in the spinal cord as an opioid and, at the same time, on the descending modulatory pathways, is expected to cover a wide range of acute and recurrent painful conditions, ranging from nociceptive inflammatory pain to neuropathic pain of moderate/severe intensity. In this review we evaluate the rationale that justifies its use as new class of pharmacological modality to treat pain accordingly also to a more update view of WHO pain ladder.